FATIGUE DAMAGE ANALYSIS OF VIBRATING SCREEN UPPER BEAM BASED ON STRAIN MODAL ANALYSIS - ZHANG ZeRong; FAN ZhiMin; WANG YongYan; YANG FuQin; XU Jun (Jixie qiangdu)
The displacement and strain modal parameters identification models of the vibrating screen were built based on modal theory,the variations of the displacement and strain modal parameters were analyzed for the vibrating screen upper beam with fatigue damage crack. The results show that the modal frequencies and the displacement mode shapes have no obvious mutation between intact and damaged upper beam,but the strain mode shapes have mutation peaks at the location of the fatigue damage crack,furthermore,the bending strain mode is more sensitive to fatigue damage crack than the twisting strain mode.Thus a fatigue damage indicator is defined by using the strain modal variable ratio between the intact and damaged upper beam,the fatigue crack size is determined by damaged degree of the upper beam,then the residual life of fatigue crack propagation of the upper beam is calculated by the Paris formula of integral form. The predictions of the damaged degree and the fatigue residual life of the vibrating screen upper beam are beneficial to dynamic optimization design,which can improve the service life of the vibrating screen.